Manifestações populares do catolicismo na Revista Eclesiástica Brasileira – 1963-1980 - David, Solange Ramos de Andrade (Revista Eclesiástica Brasileira, 2003)
A partir dos artigos publicados na Revista Eclesiástica Brasileira, a Autora aponta e analisa como a instituição eclesiástica aborda, conceitua e se posiciona perante as manifestações religiosas designadas populares durante os anos de 1963 a 1980. Dentre as principais tendências teológicas, sociológicas, antropológicas e históricas presentes nos artigos publicados, destaca a histórico-sociológica, que teve na figura do Padre José Comblin seu principal representante. Abstract: Using as her source material articles published in the Brazilian Ecclesiastical Journal (REB), the author identifies and analyses this ecclesiastical institution’s conceptualization of and its approach and position towards the so-called popular religious manifestations during the period between 1963 and 1980. Among the major theological, sociological, anthropological and historical trends present in the published articles, Ms David gives emphasis to the historical-sociological trend that had, as its main representative, Father José Comblin.